2022
DOI: 10.3390/polym14225026
|View full text |Cite
|
Sign up to set email alerts
|

Design and Ballistic Performance of Hybrid Plates Manufactured from Aramid Composites for Developing Multilayered Armor Systems

Abstract: In this study, the impact resistance of aramid fabric reinforced with shear thickening fluids (STFs), epoxy or polyurea elastomers is examined through ballistic tests. According to the ballistic test results, the aramid composite structure treated with polyurea elastomers absorbs the most impact energy per unit area density and has the best impact resistance. However, the occurrence of stress concentration during ballistic impact reduces the impact resistance of the aramid composite structure treated with epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Shih et al conducted ballistic tests to investigate the impact resistance of aramid fabrics reinforced with STFs, epoxy resins or polyurea elastomers. According to test results, the aramid composite structure treated with polyurea elastomer absorbed the most impact energy per unit area and demonstrated the best impact resistance [10].…”
Section: Military and Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Shih et al conducted ballistic tests to investigate the impact resistance of aramid fabrics reinforced with STFs, epoxy resins or polyurea elastomers. According to test results, the aramid composite structure treated with polyurea elastomer absorbed the most impact energy per unit area and demonstrated the best impact resistance [10].…”
Section: Military and Defensementioning
confidence: 99%
“…The escalating risk of terrorist attacks, military conflicts, explosive accidents and chemical disasters has heightened the necessity for blast and impact resistance in military and civilian buildings. This requirement is particularly crucial for military protective equipment such as military ships, armoured vehicles and protective helmets, all of which need to withstand shock waves and high-speed fragments resulting from near-field explosions [1][2][3][4][5][6][7][8][9][10]. Even though research on the protective properties of metal structures and high-performance fiber composites has made significant progress, there is an increasing need for lightweight and efficient blast protection structures [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The average velocity of the projectile was 415 m/s for the 50-layer composite and for the 70-layer composite, 430 m/s. In the next work, the ballistic resistance of Kevlar and Kevlar/polyurea composites on an epoxy matrix was tested at the initial speed of 410 m/s [58]. The use of this type of combination made it possible to meet the assumptions of the NIJ 0101.06 standard, however with a significant limit value of BFS.…”
Section: Comparison Of the Obtained Deflection Values To Other Matric...mentioning
confidence: 99%
“…In particular, the past decade has seen a burgeoning focus on natural fiber-reinforced polymer composites for applications in personal ballistic protection [ 7 , 8 ]. Many recent reviews and research papers have reported the ballistic performance of different lignocellulosic fibers as intermediate reinforcement layers in polymer composite multilayered armor systems (MAS) [ 9 , 10 , 11 , 12 , 13 ]. The MAS are customarily composed of at least two layers when employed against high-energy ammunition, such as 7.62 mm bullet.…”
Section: Introductionmentioning
confidence: 99%